Values Education Practices and Moral Development Experiences Among Grade 7 Learners: Perspectives from Cabagan Riverside National High School - ATTABAN, MARIA JEZEBELLE (Azal Arts and Humanities, 2026)
Values Education plays a significant role in shaping learners’ moral development, character formation, social responsibility, and ethical decision-making within the educational environment. This study explored the Values Education practices and moral development experiences among Grade 7 learners at Cabagan Riverside National High School. Anchored on Kohlberg’s Moral Development Theory and Constructivist Learning Theory, the study employed a descriptive qualitative research design to examine classroom practices, learner experiences, instructional interactions, and moral development in Values Education instruction. Participants included Grade 7 learners and Values Education teachers of Cabagan Riverside National High School. Data were gathered through semi-structured interviews, focus group discussions, classroom observations, and document analysis. Braun and Clarke’s (2006) thematic analysis approach was utilized in analyzing the gathered data. Findings revealed that reflective discussions, value-laden activities, collaborative learning experiences, role modeling, and contextualized classroom situations significantly contribute to learners’ moral awareness and behavioral engagement. Learners demonstrated increased empathy, self-awareness, social responsibility, and ethical reflection when Values Education lessons were connected to real-life experiences and community realities. The findings further revealed that supportive teacher-learner relationships and learner-centered pedagogical approaches positively influence moral development and classroom participation. However, challenges such as peer influence, inconsistent home support, limited learner participation, and difficulties in applying values in real-life situations affected values formation and classroom engagement. The study concludes that contextualized and reflective Values Education practices significantly contribute to learners’ moral development and social awareness. Strengthening experiential values formation activities, reflective classroom discussions, and collaborative school-community partnerships is recommended to improve Values Education implementation in secondary schools.